Prevalence of Heavy Menstrual Bleeding and Its Associated Cognitive Risks and Predictive Factors in Women With Severe Mental Disorders - Shan, Jianmin; Tian, Hongjun; Zhou, Chunhua; Wang, Haibo; Ma, Xiaoyan; Li, Ranli; Yu, Haiping; Chen, Guangdong; Zhu, Jingjing; Cai, Ziyao; Lin, Chongguang; Cheng, Langlang; et al. (Frontiers in Pharmacology, 2022)
Women with bipolar disorder (BP), major depressive disorder (MDD), and schizophrenia (SCZ) may experience treatment-induced heavy menstrual bleeding (HMB). HMB prevalence and associated factors were investigated in 18–34-year-old women experiencing MDD, BP, or SCZ with full insight and normal intelligence. Eighteen-month menstruation histories were recorded with pictorial blood loss assessment chart assessments of HMB. Multivariate analyses were conducted to obtain odds ratios (ORs) and 95% confidence intervals (CIs). Drug effects on cognition were assessed with the MATRICS Consensus Cognitive Battery (MCCB). HMB prevalence were: BP, 25.85%; MDD, 18.78%; and SCH, 13.7%. High glycosylated hemoglobin (HbA1c) level was a strong risk factor for HMB [BP OR, 19.39 (16.60–23.01]; MDD OR, 2.69 (4.59–13.78); and SCZ OR, 9.59 (6.14–12.43)]. Additional risk factors included fasting blood sugar, 2-h postprandial blood glucose, and use of the medication valproate [BP: OR, 16.00 (95%CI 12.74–20.22); MDD: OR, 13.88 (95%CI 11.24–17.03); and SCZ OR, 11.35 (95%CI 8.84–19.20). Antipsychotic, antidepressant, and electroconvulsive therapy use were minor risk factors. Pharmacotherapy-induced visual learning impairment was associated with HMB [BP: OR, 9.01 (95%CI 3.15–13.44); MDD: OR, 5.99 (95%CI 3.11–9.00); and SCZ: OR, 7.09 (95%CI 2.99–9.20)]. Lithium emerged as a protective factor against HBM [BP: OR, 0.22 (95%CI 0.14–0.40); MDD: OR, 0.30 (95%CI 0.20–0.62); and SCZ: OR, 0.65 (95%CI 0.33–0.90). In SCZ patients, hyperlipidemia and high total cholesterol were HMB-associated factors (ORs, 1.87–2.22). Psychiatrist awareness of HMB risk is concerningly low (12/257, 2.28%). In conclusion, prescription of VPA should be cautioned for women with mental illness, especially BP, and lithium may be protective against HMB.